Internalisasi Nilai Amanah dalam Etika Profesi Guru Bimbingan dan Konseling sebagai Upaya Pembentukan Karakter Profesional di MAN Salatiga - Elsa Ainun Salma; Ramadhani Yudha Afifi; Nabila Salma Kasih Muwuri (Kampus Akademik Publiser, 2026)
Abstract. This study aims to examine the internalization process of the amanah (trustworthiness) value within the professional ethics of Guidance and Counseling (GC) teachers at MAN Salatiga and its contribution to the formation of professional character. A descriptive qualitative approach was employed, with data collected through semi-structured in-depth interviews, passive participatory observation, and documentation involving six research subjects selected through purposive sampling: two GC teachers as primary informants, the principal and vice principal as supporting informants, and two students as triangulation informants. Data validity was ensured through source and technique triangulation, while data analysis followed the interactive model of Miles and Huberman. The findings reveal that the internalization of the amanah value among GC teachers at MAN Salatiga has taken place simultaneously across three levels: cognitive, affective, and behavioral. At the cognitive level, GC teachers understand amanah as a fundamental ethical principle of the profession. At the affective level, it is experienced as an integral part of professional identity. At the behavioral level, it is manifested through concrete practices such as the use of client coding systems, maintaining confidentiality, and professional coordination without disclosing student identities. From the students’ perspective, GC teachers who embody amanah are perceived as figures who create a safe zone, enabling students to openly share their personal issues. The internalization process primarily occurs through authentic moral modeling and personal interaction within the Islamic institutional context of the madrasah. This study affirms that amanah is not merely a formal ethical obligation but constitutes the core of professional character for GC teachers, with direct implications for service quality and student character development. Keywords: Value internalization, amanah, professional ethics, guidance and counseling teacher, professional character Abstrak. Penelitian ini bertujuan untuk mengkaji proses internalisasi nilai amanah dalam etika profesi guru Bimbingan dan Konseling (BK) di MAN Salatiga serta kontribusinya terhadap pembentukan karakter profesional. Penelitian menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui wawancara mendalam semi-terstruktur, observasi partisipatif pasif, dan dokumentasi. Subjek penelitian dipilih secara purposive sampling, melibatkan dua guru BK sebagai informan utama, kepala sekolah dan wakil kepala sekolah sebagai informan pendukung, serta dua peserta didik sebagai informan triangulasi. Keabsahan data dijamin melalui triangulasi sumber dan teknik, sedangkan analisis dilakukan menggunakan model interaktif Miles dan Huberman. Hasil penelitian menunjukkan bahwa internalisasi nilai amanah pada guru BK di MAN Salatiga telah berlangsung pada tiga level secara bersamaan, yaitu kognitif, afektif, dan behavioral. Pada level kognitif, guru BK memahami amanah sebagai prinsip etik profesi yang fundamental. Pada level afektif, amanah dihayati sebagai bagian dari identitas profesional. Pada level behavioral, amanah diwujudkan melalui praktik nyata seperti penggunaan sistem kode konseli, penjagaan kerahasiaan, dan koordinasi profesional tanpa membuka identitas siswa. Dari perspektif siswa, guru BK yang amanah dipersepsi sebagai figur yang menciptakan safe zone sehingga siswa merasa aman untuk membuka diri. Proses internalisasi berlangsung terutama melalui keteladanan moral yang otentik dan interaksi personal, dengan kuatnya dimensi keislaman sebagai penguat motivasi internal dalam konteks madrasah. Penelitian ini menegaskan bahwa nilai amanah bukan sekadar kewajiban etik formal, melainkan inti karakter profesional guru BK yang berdampak langsung pada kualitas layanan dan pembentukan karakter siswa. Kata kunci: Internalisasi nilai, amanah, etika profesi, guru bimbingan dan konseling, karakter profesional